1993
DOI: 10.1002/chin.199324272
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Ruthenium‐Catalyzed Reconstitutive Condensation. Application to Functionalized Steroid Side Chains.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…First B. M. Trost showed that using the CpRu(PPh 3 ) 2 Cl/NH 4 PF 6 catalytic system, the addition of allylic alcohols to terminal alkynes was possible and took place affording b,c-unsaturated ketones, via addition of allyl alcohol to the vinylidene intermediate and C-O bond cleavage and allyl migration (Eq. 14) [74][75][76][77].…”
Section: ð12þmentioning
confidence: 99%
“…First B. M. Trost showed that using the CpRu(PPh 3 ) 2 Cl/NH 4 PF 6 catalytic system, the addition of allylic alcohols to terminal alkynes was possible and took place affording b,c-unsaturated ketones, via addition of allyl alcohol to the vinylidene intermediate and C-O bond cleavage and allyl migration (Eq. 14) [74][75][76][77].…”
Section: ð12þmentioning
confidence: 99%